ZBED3 exacerbates hyperglycemia by promoting hepatic gluconeogenesis through CREB signaling - Luo, Yuan-yuan; Ruan, Chang-shun; Zhao, Fu-zhen; Yang, Min; Cui, Wei; Cheng, Xi; Luo, Xiao-he; Zhang, Xian-xiang; Zhang, Cheng (Metabolism, clinical and experimental, 2025)
Elevated hepatic glucose production (HGP) is a prominent manifestation of impaired hepatic glucose metabolism in individuals with diabetes. Increased hepatic gluconeogenesis plays a pivotal role in the dysregulation of hepatic glucose metabolism and contributes significantly to fasting hyperglycemia in diabetes. Previous studies have identified zinc-finger BED domain-containing 3 (ZBED3) as a risk gene for type 2 diabetes (T2DM), and its single nucleotide polymorphism (SNPs) is closely associated with the fasting blood glucose level, suggesting a potential correlation between ZBED3 and the onset of diabetes. This study primarily explores the effect of ZBED3 on hepatic gluconeogenesis and analyzes the relevant signaling pathways that regulate hepatic gluconeogenesis. The expression level of ZBED3 was assessed in the liver of insulin-resistant (IR)-related disease. RNA-seq and bioinformatics analyses were employed to examine the ZBED3-related pathway that modulated HGP. To investigate the role of ZBED3 in hepatic gluconeogenesis, the expression of ZBED3 was manipulated by upregulation or silencing using adeno-associated virus (AAV) in mouse primary hepatocytes (MPHs) and HHL-5 cells. In vivo, hepatocyte-specific ZBED3 knockout mice were generated. Moreover, AAV8 was employed to achieve hepatocyte-specific overexpression and knockdown of ZBED3 in C57BL/6 and db/db mice. Immunoprecipitation and mass spectrometry (IP-MS) analyses were employed to identify proteins that interacted with ZBED3. Co-immunoprecipitation (co-IP), glutathione S-transferase (GST) - pulldown, and dual-luciferase reporter assays were conducted to further elucidate the underlying mechanism of ZBED3 in regulating hepatic gluconeogenesis. The expression of ZBED3 in the liver of IR-related disease models was found to be increased. Under the stimulation of glucagon, ZBED3 promoted the expression of hepatic gluconeogenesis-related genes PGC1A, PCK1, G6PC, thereby increasing HGP. Consistently, the rate of hepatic gluconeogenesis was found to be elevated in mice with hepatocyte-specific overexpression of ZBED3 and decreased in those with ZBED3 knockout. Additionally, the knockdown of ZBED3 in the liver of db/db mice resulted in a reduction in hepatic gluconeogenesis. Moreover, the study revealed that ZBED3 facilitated the nuclear translocation of protein arginine methyltransferases 5 (PRMT5) to influence the regulation of PRMT5-mediated symmetrical dimethylation of arginine (s-DMA) of cyclic adenosine monophosphate (cAMP) response element binding protein (CREB), which in turn affects the phosphorylation of CREB and ultimately promotes HGP. This study indicates that ZBED3 promotes hepatic gluconeogenesis and serves as a critical regulator of the progression of diabetes. [Display omitted] •Increased expression of ZBED3 is observed in insulin-resistant (IR) liver tissues.•ZBED3 plays a critical role in regulating diabetes progression by promoting hepatic gluconeogenesis.•ZBED3 promotes PRMT5's nuclear translocation, enhancing CREB phosphorylation and hepatic gluconeogenesis.